1994
DOI: 10.2214/ajr.163.5.7976880
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of inflammatory pseudotumor of the liver: value of CT.

Abstract: OBJECTiVE.Inflammatory pseudotumor of the liver is a localized mass consisting of a fibrous stroma and chronic inflammatory infiltrate without anaplasia. Diagnosis of this rare disease Is important to avoid surgery. The purpose of this study was to determine if CT is useful in the diagnosis of this lesion.SUBJECTS AND METHODS. CT scans of nine patients with a proved diagnosis of inflammatory pseudotumor of the liver were reviewed. Diagnosis was made by the surgical resection In three patients and by percutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
2
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 18 publications
4
80
2
3
Order By: Relevance
“…Previous studies have noted that delayed-phase CT and fluorodeoxyglucose positron emission tomography do not distinguish hepatic IPT from malignant tumors (16,17). The present case is the first case reported in which the IPT was hypodense at the hepatobiliary phase of Ga-EOB-DTPA-enhanced MRI.…”
contrasting
confidence: 50%
“…Previous studies have noted that delayed-phase CT and fluorodeoxyglucose positron emission tomography do not distinguish hepatic IPT from malignant tumors (16,17). The present case is the first case reported in which the IPT was hypodense at the hepatobiliary phase of Ga-EOB-DTPA-enhanced MRI.…”
contrasting
confidence: 50%
“…9,10 Although some reports mention a decrease in the size of the lesions as shown by follow-up imaging studies, we found no other case in the literature with imaging before, during, and after. 8 Moreover, in our follow-up ultrasonographic and CT scans the caudate lobe appears to have shrunk. This may be due to postinflammatory fibrosis and can hypothetically represent the healing process of this lesion.…”
mentioning
confidence: 66%
“…This is most likely due to the variable vascularity of the lesion, which ranges from avascular to hypervascular. [7][8][9][10] The ultrasonographic findings of IPT are also variable. Most lesions reported were described as well circumscribed, with either hypoechogenicity or hyperechogenicity.…”
mentioning
confidence: 99%
“…Gerçek sebebi bilinmese de enfeksiyon ve biliyer obstrüksiyon en olası sebepler olarak ileri sürülmektedir. Karaciğer IPT'si sıklıkla tek bir soliter (%81), nadiren de multiple (%19) lezyonlar şeklinde gözlenirler [26,27]. Akciğerde gözlenen psödotümörün aksine karaciğer IPT'si epigastrik ağrı, ateş, kusma ve kilo kaybı gibi bir ya da birden çok sistemik semptomla presente olur.…”
Section: İnflamatuar Myofibroblastik Tümör (İnflamatuar Psödotümör)unclassified